Interprofessional collaboration during a specialised mobile palliative care service pilot in the rural area of Lucerne. - Sahra Maria Anna Bucher; Anne Marie Schumacher Dimech; Beat Müller; Patrick E Beeler (PLoS ONE)
Interprofessional collaboration in outpatient palliative care is critical to ensuring good quality of care in the home care sector. We investigated facilitators and barriers (FaBs) of interprofessional collaboration among healthcare professionals who participated in a 6-month pilot of a newly implemented specialised mobile palliative care service (SMPCS) in rural Lucerne. This study used a mixed-methods approach to collect (i) qualitative data on FaBs as perceived by nurses and primary care physicians (PCPs), and (ii) quantitative data across the entire interprofessional collaboration using a validated questionnaire expanded with 10 specific questions about the pilot. Identified facilitators of interprofessional collaboration were (i) use of standardised documents, (ii) clear allocation of responsibilities, (iii) regular exchange and clear communication and (iv) consideration of care coordination. Reported barriers were (i) a deficit of knowledge and experience of palliative care among PCPs and (ii) time constraints. This study provides valuable insights into FaBs of interprofessional collaboration in palliative care. Several recommendations can be drawn for how interprofessional collaboration may be optimised. Awareness of FaBs and their consideration in the implementation phase of new services can strengthen the foundation for a successful interprofessional collaboration.